2021
DOI: 10.1038/s41598-020-80928-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation and comparison of coronary artery characteristics by 3D coronary volume reconstruction

Abstract: Non-atherosclerotic abnormalities of vessel calibre, aneurysm and ectasia, are challenging to quantify and are often overlooked in qualitative reporting. Utilising a novel 3-dimensional (3D) quantitative coronary angiography (QCA) application, we have evaluated the characteristics of normal, diabetic and aneurysmal or ectatic coronary arteries. We selected 131 individuals under 50 years-of-age, who had undergone coronary angiography for suspected myocardial ischaemia between 1st January 2011 and 31st December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In their approach to construct the arteries, the diameter of the vessel was evaluated utilizing automatic detection of the change in contrast and manually corrected when it needs. Two angiographic images at different angles were also used in Kim et al 8 to construct 3D coronary artery. In this case, a manual approach was used to define the start and end points of the segment of interest and extract contours and centerlines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their approach to construct the arteries, the diameter of the vessel was evaluated utilizing automatic detection of the change in contrast and manually corrected when it needs. Two angiographic images at different angles were also used in Kim et al 8 to construct 3D coronary artery. In this case, a manual approach was used to define the start and end points of the segment of interest and extract contours and centerlines.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Many works have been carried out to obtain the 3D reconstruction of the blood vessels from various image devices and the missing depth data of the captured images is then investigated in studies that focus on the vessels' topology. [6][7][8] New blood vessel segmentation algorithms are currently being developed since segmentation is an essential step in constructing the geometry of the blood vessel. 2,9,10 Generating the blood vessel's centerline and determining each bifurcation point along the vessel tree is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…A 3D construction is possible using computed tomography (CT), but it is difficult to perform the examination in a standing position. Currently, a number of studies have reported the feasibility of 3D reconstruction of coronary arteries from multiple angiographic projections in the field of interventional cardiology [4][5][6]. In this study, we propose a method to reconstruct the 3D shape of a pacing lead from radiographs taken at 90-degree angles.…”
Section: Introductionmentioning
confidence: 99%